2004
DOI: 10.1128/aac.48.8.3051-3056.2004
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Thrombin-Induced Platelet Microbicidal Protein Is Associated with Increased Fluconazole Efficacy against Experimental Endocarditis Due to Candida albicans

Abstract: Platelet microbicidal proteins (PMPs) are believed to be integral to host defense against endovascular infection. We previously demonstrated that susceptibility to thrombin-induced PMP 1 (tPMP-1) in vitro negatively influences Candida albicans virulence in the rabbit model of infective endocarditis (IE). This study evaluated the relationship between in vitro tPMP-1 susceptibility (tPMP-1 s ) or resistance (tPMP-1 r ) and efficacy of fluconazole (FLU) therapy of IE due to C. albicans. Candida IE was established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…C. albicans ATCC 36082, originally a clinical isolate, was previously determined to be susceptible to the antimicrobial peptide tPMP-1 (tPMP-1 S ; strain 36082 S ) (41). A stable tPMP-1-resistant and orthogenic coun-terpart (tPMP-1 R ) of strain 36082 S , designated strain 36082 R , has been characterized previously (42,43). Prior studies demonstrated that other than in differences in tPMP-1 susceptibility profiles, the 36082 S and 36082 R strains are indistinguishable by genotyping and immunotypic profiling, assessment of endothelial cell adhesion, and metabolic, germination, or growth rate characteristics (41)(42)(43).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…C. albicans ATCC 36082, originally a clinical isolate, was previously determined to be susceptible to the antimicrobial peptide tPMP-1 (tPMP-1 S ; strain 36082 S ) (41). A stable tPMP-1-resistant and orthogenic coun-terpart (tPMP-1 R ) of strain 36082 S , designated strain 36082 R , has been characterized previously (42,43). Prior studies demonstrated that other than in differences in tPMP-1 susceptibility profiles, the 36082 S and 36082 R strains are indistinguishable by genotyping and immunotypic profiling, assessment of endothelial cell adhesion, and metabolic, germination, or growth rate characteristics (41)(42)(43).…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies demonstrated that other than in differences in tPMP-1 susceptibility profiles, the 36082 S and 36082 R strains are indistinguishable by genotyping and immunotypic profiling, assessment of endothelial cell adhesion, and metabolic, germination, or growth rate characteristics (41)(42)(43). Studies have also confirmed that the tPMP-1 S and tPMP-1 R phenotypes are stable in vitro following passage in media or serum and upon passage through experimental animal models (42,43). Moreover, prior investigations in vivo confirmed that these strains are equivalent in their interactions with platelets or cardiac vegetations and do not differ in rates of clearance after hematogenous inoculation in experimental animal models (9,42).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations